Addressing gaps in AMR awareness in the public: an evidence-based policy brief to guide school curriculum review in Uganda - JP Waswa; Reuben Kiggundu; Mohan P. Joshi; Joseph Mpagi; Hassan Kasujja; Marion Murungi; Henry Kajumbula; Esther Were; Dan Schwarz; Kamada Lwere; Kamada Lwere; Niranjan Konduri (Frontiers Media S.A., 2023)
The government of Uganda, through its Ministry of Health, previously adopted curriculum review as a mechanism to respond to public health threats such as HIV/AIDS and include content in primary and secondary schools. This approach contributes to raising public awareness, a key strategy recommended by the World Health Organization to support the global response to the threat of antimicrobial resistance (AMR). This policy brief, developed for policymakers related to school curricula, aims to advocate for and support integration of AMR content in Uganda's primary and secondary level school curricula. The policy brief supports efforts by the multisectoral National AMR Subcommittee to create awareness on this issue as part of its role in facilitating the operationalization of Uganda's National Action Plan on AMR.